Dogs with Acute Myeloid Leukemia Have Clonal Rearrangements in T and B Cell Receptors - Stokol, Tracy; Nickerson, Gabrielle A.; Shuman, Martha; Belcher, Nicole (Frontiers in Veterinary Science, 2017)
Clonality testing for rearrangements in the complementarity-determining region 3 of the immunoglobulin heavy chain of B lymphocytes (B cell receptor) and the T cell receptor of T lymphocytes helps distinguish between clonal and non-clonal expansions of lymphocytes. There are rare reports of clonally rearranged T and B cell receptors in dogs with acute myeloid leukemia (AML). Our objective was to determine the frequency of clonally rearranged T and B cell receptors in dogs with AML. Archived slides from historical cases of AML (from January 2010 to June 2013) and slides or liquid specimens (blood, bone marrow, body cavity fluid or tissue aspirates) from cases of AML diagnosed between June 2013 and February 2017 were used in the study. A diagnosis of AML was made on the basis of more than 20% immature neoplastic cells (“blasts”) in blood, bone marrow or extramedullary tissues, displaying features of myeloid differentiation. Myeloid differentiation was based on a combination of morphologic criteria, positive flow cytometric labeling for surface antigens typical of myeloid origin (e.g. CD11b, CD11c, CD14 with a general lack of expression of T or B cell markers), or positive cytochemical staining reactions for myeloid-associated enzymes (e.g. alkaline phosphatase, chloroacetate esterase). There were 63 cases of AML diagnosed during this period, however slides or liquid specimens with sufficient DNA for testing were only obtained from 25 dogs. Affected dogs represented various breeds and were a median of 8 years old, with more male (64%) than female (36%) dogs. Common clinical signs were peripheral or internal lymphadenopathy (10/25 dogs, 40%) and hepatomegaly or splenomegaly (10/25 dogs combined, 40%). Typical hematologic findings were bi- or pancytopenia (23/25 dogs, 92%), with circulating blasts (21/25, 84%). Solitary clonal (4 B cell, 6 T cell) and biclonal (6 B and T cell) rearrangements in B or T cell receptors were found in 16 dogs (64%). Our results indicate that dogs with AML can have a high frequency of clonally rearranged T or B cell receptors, including biclonality, and clonality testing should not be used as a tool to distinguish between acute leukemia of myeloid or lymphoid origin.